Bell's Palsy: Symptoms Preceding and Accompanying the Facial Paresis. (27th November 2014) - De Seta, Daniele; Mancini, Patrizia; Minni, Antonio; Prosperini, Luca; De Seta, Elio; Attanasio, Giuseppe; Covelli, Edoardo; De Carlo, Andrea; Filipo, Roberto
Abstract : This individual prospective cohort study aims to report and analyze the symptoms preceding and accompanying the facial paresis in Bell's palsy (BP). Two hundred sixty-nine patients affected by BP with a maximum delay of 48 hours from the onset were enrolled in the study. The evolution of the facial paresis expressed as House-Brackmann grade in the first 10 days and its correlation with symptoms were analyzed. At the onset, 136 patients presented postauricular pain, 114 were affected by dry eye, and 94 reported dysgeusia. Dry mouth was present in 54 patients (19.7%), facial pain, hyperlacrimation, aural fullness, and hyperacusis represented a smaller percentage of the reported symptoms. After 10 days, 39.9% of the group had a severe paresis while 10.2% reached a complete recovery. Dry mouth at the onset was correlated with severe grade of palsy and was prognostic for poor recovery in the early period. These outcomes lead to the deduction that the nervus intermedius plays an important role in the presentation of the BP and it might be responsible for most of the accompanying symptomatology of the paresis. Our findings could be of important interest to early address a BP patient to further examinations and subsequent therapy.